SETARIA IN A FREE-RANGE MALE SPOTTED DEER (AXIS AXIS): A CASE REPORT - S.T. Bino Sundar; K. Rajeshkumar; S. Shiyamala; M. Aravind; K. Jeeva; B. Nishanth; P.N. Richard Jagatheesan (Indian Journal of Veterinary and Animal Sciences Research, 2026)
The occurrence of Setaria digitata in the pleural and peritoneal cavities of a free-range male spotted deer (Axis axis) observed during necropsy is reported.A total of 25 worms were recovered out of which 23 were female worms and 2 were male worms. The worms were found in the visceral organs of the pleural cavity and peritoneal cavity. Only one female worm was found in the pleural cavity whereas all the other worms were found in the peritoneal cavity. One worm in the peritoneal cavity was found embedded in a patch of inflammatory tissue. The worms were morphologically identified as Setaria digitata. Cranial ends of both male and female worms had a central helmet with triangular lateral lips. In male worms, the cuticle was corrugated with a coiled caudal end possessing a pair of light brown-coloured unequal spicules, the right spicule was stout and thick with narrow proximal end and the left spicule had a shaft and blade. In female worms, the cuticle was smooth and tail had a smooth knob with lateral appendages. The present will help to map the status of nematode infection in spotted deers in wild and to frame strategies for control of setariosis in spotted deers.